Neurosarcoidosis in a Tertiary Referral Center: A Cross-Sectional Cohort Study. Issue 14 (April 2016) - Leonhard, Sonja E.; Fritz, Daan; Eftimov, Filip; van der Kooi, Anneke J.; van de Beek, Diederik; Brouwer, Matthijs C.
Abstract : Abstract: The aim of this study was to evaluate clinical characteristics, diagnostic strategy, and treatment in patients with neurosarcoidosis in a tertiary referral centre. In a cross-sectional study, we included all patients with neurosarcoidosis treated at our tertiary referral center between September 2014 and April 2015. We identified 52 patients, among them 1 patient was categorized as having definite neurosarcoidosis, 37 probable neurosarcoidosis, and 14 possible neurosarcoidosis. Neurologic symptoms were the first manifestation of sarcoidosis in 37 patients (71%). Chronic aseptic meningitis was the most common presentation (19/52 patients [37%]), followed by cranial neuropathy (16/52 patients [31%]). Serum angiotensin-converting enzyme and lysozyme levels were elevated in 18 of 41 (44%) and 12 of 26 cases (46%). Pulmonary or lymph node sarcoidosis was identified by chest X-ray in 21 of 39 cases (54%) and by computed tomography of the chest in 25 of 31 cases (81%); 18 Fluorodeoxyglucose-Positron emission tomography showed signs of sarcoidosis in 15 of 19 cases (79%). Thirty-one of the 46 cases receiving treatment (67%) improved, 13 cases (28%) stabilized, and 2 cases (4%) deteriorated. First-line treatment with corticosteroids resulted in satisfactory reduction of symptoms in 21 of 43 patients (49%). Seventeen patients (33%) needed second-line cytostatic treatment, and 10 patients (19%) were treated with tumor necrosis factor-α inhibitors. The majority of patients with neurosarcoidosis present with chronic meningitis without a history of systemic sarcoidosis. The diagnosis can be difficult to make because of the poor sensitivity of most diagnostic tests. Half of patients had a satisfactory reduction of symptoms on first-line therapy. Abstract : Supplemental Digital Content is available in the text